Influence of National Culture on Accounting Conservatism and Risk-Taking in the Banking Industry - Kanagaretnam, Kiridaran; Lim, Chee Yeow; Lobo, Gerald J. (The Accounting Review, 2014)
ABSTRACT Using an international sample of banks and country-level indices for individualism and uncertainty avoidance as proxies for national culture, we study how differences in culture across countries affect accounting conservatism and bank risk-taking. Consistent with expectations, our cross-country analysis indicates that individualism is negatively (positively) related to conservatism (risk-taking) and uncertainty avoidance is positively (negatively) related to conservatism (risk-taking). We also find that cultures that encourage higher risk-taking experienced more bank failures and bank troubles during the recent financial crisis. Data Availability: Data are available from the sources identified in the text.